Repetizione con Moto pada Interior âHouse of Musicâ di Surabaya - Sriti Mayang Sari, Yoviena Suminto (Intra, 2013)
Music booming across the country, including in Indonesia, especially in Surabaya. Many music schools that provide for the needs of the musicians in Surabaya. However, the licensed music school Yamaha Musik Indonesia most in demand because they have the international standards for curriculum use. The design of âHouse of Musicâ is intended to accommodate the educational needs of the musicians, especially in the area of West Surabaya. In addition, the application of the concept of Repetizione con Moto on the interior makes "House of Music" is different than the other Yamaha music school. This concept is the application of the tones are repeated only with different pitch. Given this concept, the musicians are expected to perform in the musical activity in the "House of Music" comfortably.